Pyrrolidine-based catalytic microporous polymers in sustainable CN and CC bond formation via iminium and enamine activation. (June 2022) - Vargas, E.L.; Esteban, N.; Cencerrero, J.; Francés, V.; Álvarez, C.; Miguel, J.A.; Gallardo, A.; Lozano, A.E.; Cid, M.B.
Abstract: A new set of catalytic materials having a pyrrolidine moiety confined in microporous organic polymer networks (POPs) has been attained. These catalytic polymers have been prepared by a straightforward synthesis starting from microporous polymer networks made from isatin (or a mixture of isatin and trifluoroacetophenone) and 1, 3, 5-triphenylbenzene. The polymers efficiently catalyzed the formation of nitrones under very mild and sustainable conditions using green solvents through an iminium ion activation mechanism. The reactions are scalable, and polymers are easily recycled. Special attention has been paid to understanding all the factors that could affect the efficiency of the confined catalysts. The electronic and conformational characteristics of the pyrrolidine moiety attached to the porous polymers, as well as other features that could affect the transport through the network, such as molecular volume and shape of reactants and products, and even hydrophilic or hydrophobic properties, have been systematically evaluated. In addition, the heterogeneous polymers are also useful in CC bond formation through both iminium ion and enamine activation. Highlights: New microporous polymer networks with confined pyrrolidine groups, POPs, were prepared. The materials were easy to prepare and showed high thermal and chemical stability. POPs act as efficient and sustainable heterocatalysts in CN and CC bond formation. Experimental/theoretical studies provide insight into the structure/properties of POPs. Catalysis of POPs depends on volume/shape/hydrophilicity rather than electronic effects.